Research the patterns of path representation in Chinese based on spatial cognition: Illustrated by the example of capital normal university - Dapeng Zhang; Jing Zhang; Lianjun Zhang; Gege Yang; Jiefeng Jiang (2010 18th International Conference on Geoinformatics, 2010)
In this paper, we do research on the patterns of path representation in Chinese language from the perspective of spatial cognition. At first, we acquire Chinese sentences of path representation in the form of questionnaire. In the data processing stage, we extract the trunk of each sentence have acquired and statistic the rules of words used in these sentences. Then we establish the knowledgebase of path representation in Chinese. According to the character "Phrases compose sentence" in Chinese, we put forward to the method that define description phrases of path on this basis of knowledgebase first, furthermore compose the sentence of path representation by assembling the description phrases together following a certain pattern.